2003
DOI: 10.1128/jb.185.18.5639-5642.2003
|View full text |Cite
|
Sign up to set email alerts
|

Disparate Oxygen Responsiveness of Two Regulatory Cascades That Control Expression of Symbiotic Genes in Bradyrhizobium japonicum

Abstract: Two oxygen-responsive regulatory systems controlling numerous symbiotic genes in Bradyrhizobium japonicum were assayed in free-living cultures for their capacity to activate target genes under different oxygen conditions. NifA-and FixLJ-controlled target genes showed disparate relative expression patterns. Induction of NifA-dependent genes was observed only at oxygen concentrations below 2% in the gas phase, whereas that of FixLJ-controlled targets progressively increased when the oxygen concentration was lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 29 publications
1
77
2
Order By: Relevance
“…S1, lanes 1-3). This result was unexpected, because previous studies showed a clear induction of fixK 2 gene expression in response to decreased oxygen concentrations, although a basal level of fixK 2 expression had been noticed even in aerobiosis (16,17,20 H2O2 sensitivity of the B. japonicum WT and the C183A-FixK2-expressing mutant strain 8854. Soft agar (0.9%) plates with PSY medium were inoculated with the indicated B. japonicum strains.…”
Section: Analysis Of the In Vivo Status Of The Fixk2contrasting
confidence: 39%
“…S1, lanes 1-3). This result was unexpected, because previous studies showed a clear induction of fixK 2 gene expression in response to decreased oxygen concentrations, although a basal level of fixK 2 expression had been noticed even in aerobiosis (16,17,20 H2O2 sensitivity of the B. japonicum WT and the C183A-FixK2-expressing mutant strain 8854. Soft agar (0.9%) plates with PSY medium were inoculated with the indicated B. japonicum strains.…”
Section: Analysis Of the In Vivo Status Of The Fixk2contrasting
confidence: 39%
“…Upon a switch to low-oxygen or anoxic conditions, the redox-responsive NifA protein in concert with RNA polymerase containing RpoN ( 54 ) enhances its own synthesis via activation of the Ϫ24/Ϫ12-type P1 promoter. This results in maximal expression not only of the fixR-nifA operon but also of other target genes (11,51). Most recently, the NifA-RpoN regulon of B. japonicum was unraveled by a genome-wide transcriptome analysis, which identified numerous new NifA-RpoN-dependent genes (25).…”
mentioning
confidence: 99%
“…In these two cascades, different oxygen-sensing mechanisms are responsible for a stepwise activation of downstream events (63). In the RegSR-NifA cascade, the low-oxygen-responsive NifA protein activates the transcription of essential symbiotic nitrogen fixation genes at an oxygen concentration at or below 0.5% oxygen in the gas phase over a culture.…”
mentioning
confidence: 99%